KAJIAN POLITIK HUKUM TERHADAP TRANSPLANTASI HUKUM DI ERA GLOBAL - Muhdlor, A Zuhdi (Jurnal Hukum dan Peradilan, 2016)
The adoption of a law has long historical roots, it was long before developing colonization by western countries. The ultimate goal is to sink deeper into the clutches of colonial country in all fields, including if one day the colonies are now independent. But in the global era where life organizations increasingly shifted from local to national, and even international, and increasingly contractual the adoption of a law precisely become a necessity. A nation might be isolated from the world community without the adoption of a law. No exception to Islamic law, although basically rejected the adoption, but with different approaches ijtihad, there is always a way to accept new ideas so as to keep shalih li kulli wal - makan.Keywords: the politic of law, the adoption of a las, global era